Answer:
-3/2
Explanation:
(1/2)/(2/-5) +(-1/4) = (1/2)·(-5/2) -(1/4) . . . . invert the denominator and multiply
= -5/4 -1/4 = -6/4 . . . . . . . . . . . . . . . . . .add the two terms
= -3/2 . . . . . reduce the fraction
_____
Comment on fraction division
There are two ways to divide fractions. In the end, they amount to the same thing.
One: multiply by the inverse of the denominator:
(a/b) / (c/d) = (a/b)·(d/c) = (ad)/(bc)
Two: adjust the denominators to be the same, then use the ratio of numerators:
(a/b) / (c/b) = a/c
__
Here, we could rewrite the fractions as ...
(5/10) / (-4/10) = -5/4 . . . . using method two